Experimental Study on the Influence of a Cementitious Permeable Crystallization Admixture (CPCA) in Improving Concrete Durability - Yu-chuan Yang; Hai-bo Li; Xing-guo Yang; Shi-quan Chen; Jia-wen Zhou (Advances in Civil Engineering)
The corrosion of steel reinforcement in reinforced concrete is a serious problem affecting the durability of concrete structures. And the steel corrosion caused by chloride ion erosion is the most serious damage to reinforced concrete structures, which affects the safety and service life of the structure. In order to prevent steel corrosion caused by chloride, it is necessary to pay more attention to chloride ion penetration damage. At present, the most commonly used method is to use additives in concrete structures, so as to improve the durability of concrete by reducing its permeability coefficient. Cement-based permeable crystalline admixtures can effectively improve the impermeability and mechanical properties of concrete by complex crystallization reactions between reactive chemicals and cement gels. In the paper, the Penetron admix 803 was selected as a typical CPCA in the experimental study, and the rapid chloride migration (RCM) experiments and mechanics experiments were carried out for four concrete structures with different dosages of Penetron admix 803 (PA8). Compared with plain concrete, the concrete structure containing PA8 makes it difficult for water and other liquids to enter by filling micropores and shrinkage cracks by scanning electron microscope test, so its impermeability is greatly improved. And concrete structure containing permeable crystalline admixture can reduce chloride ion permeability effectively. The experimental results showed that with the increase of PA8 content, the diffusion coefficient of the concrete structure decreased rapidly from 45.8 × 10−12 m2/s to 17.7 × 10−12 m2/s, while the service life of concrete structures increased continuously. And the mechanism of the chemical reaction between PA8 and the internal components of concrete structure was revealed, which was mainly due to the catalytic reaction between the reactive chemicals of PA8 and the cement hydrates of concrete structure forming insoluble crystals filled with concrete micropores. Experimental and theoretical results indicate that the permeable crystalline admixture can greatly improve the chloride-related durability and mechanical properties of the concrete structure.